Contributions of dopamine-related basal ganglia neurophysiology to the developmental effects of incentives on inhibitory control. (April 2022) - Parr, Ashley C.; Calabro, Finnegan; Tervo-Clemmens, Brenden; Larsen, Bart; Foran, Will; Luna, Beatriz
Abstract: Inhibitory control can be less reliable in adolescence, however, in the presence of rewards, adolescents' performance often improves to adult levels. Dopamine is known to play a role in signaling rewards and supporting cognition, but its role in the enhancing effects of reward on adolescent cognition and inhibitory control remains unknown. Here, we assessed the contribution of basal ganglia dopamine-related neurophysiology using longitudinal MR-based assessments of tissue iron in rewarded inhibitory control, using an antisaccade task. In line with prior work, we show that neutral performance improves with age, and incentives enhance performance in adolescents to that of adults. We find that basal ganglia tissue iron is associated with individual differences in the magnitude of this reward boost, which is strongest in those with high levels of tissue iron, predominantly in adolescence. Our results provide novel evidence that basal ganglia neurophysiology supports developmental effects of rewards on cognition, which can inform neurodevelopmental models of the role of dopamine in reward processing during adolescence. Highlights: During adolescence, reward incentives enhance inhibitory control to adult levels. Indirect basal ganglia tissue iron measures reflecting dopamine availability support adolescent reward related cognitive enhancement. Dopamine-related basal ganglia neurophysiology supports developmental effects of rewards on inhibitory control.